Composition of sharp-focused image by rotation of Scheimpflug camera. (November 2022) - Yi, Sooyeong; Min, Sungjae
Highlights: Slanted subject plane is focused if an image sensor is non-parallel with a lens. A volume of subject space can be sharply focused by rotating the Scheimpflug camera. Sharp-focused image is composed by selecting focused pixels based on focus measure. Abstract: A Scheimpflug camera has an image sensor tilted intentionally with respect to the lens. As the sensor and the lens are not parallel, the sharp-focused subject plane is slanted with respect to the camera according to the lens formula; this is known as the Scheimpflug principle. Therefore, if the camera is rotated about the optical axis, the sharp-focused plane covers a volume of the subject space. In this study, an application of the Scheimpflug camera is proposed to obtain a sharp-focused image with an extended depth of field (DOF) everywhere in the image. Off-the-shelf optical parts are used to implement the camera. A set of images are acquired by rotating the camera about an optical axis and the sharp-focused image is composed by selecting the focused pixels in the set of original images based on the focus measure. The experimental results show that the final composed image has a sharp focus in every region although each original image has a regional blur in the image plane. The focus measure of the composed image is 3–4 times higher than that of the original images.